2001
DOI: 10.4049/jimmunol.167.4.1970
|View full text |Cite
|
Sign up to set email alerts
|

Human Recent Thymic Emigrants–Identification, Expansion, And Survival Characteristics

Abstract: This study shows that, in humans at birth, circulating T cells represent recent thymic emigrants (RTEs) as reflected in their high level of expression of TCR excision circles. RTEs express “thymocyte-like” characteristics with regard to rapid rate of apoptosis. In the presence of common γ-chain cytokines, in particular IL-7, they show enhanced potential to survive, entry into cell cycle, and proliferation. Although common γ-chain cytokines were also potent antiapoptotic stimuli for mature adult-derived naive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
133
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 41 publications
7
133
3
1
Order By: Relevance
“…These cytokines, which include IL-2, IL-4, and IL-7, play a vital role in the development, expansion, and survival of the lymphoid system (11). Previous work by our group and others has shown that IL-7 can induce expansion and survival of these cells while maintaining a naive phenotype (6,10,12). The antiapoptotic effect of IL-7 has been shown to be in part due to its up-regulation of the antiapoptotic protein Bcl-2 (13,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These cytokines, which include IL-2, IL-4, and IL-7, play a vital role in the development, expansion, and survival of the lymphoid system (11). Previous work by our group and others has shown that IL-7 can induce expansion and survival of these cells while maintaining a naive phenotype (6,10,12). The antiapoptotic effect of IL-7 has been shown to be in part due to its up-regulation of the antiapoptotic protein Bcl-2 (13,14).…”
mentioning
confidence: 99%
“…CD4 ϩ , CD45RA ϩ naive T cells, described as recent thymic emigrants (RTEs), 2 express a number of characteristics that distinguish them from naive T cells that are present later in life. They express high levels of the thymus-associated Ag CD38 and are characterized by decreased proliferative responses to Ag stimulation, decreased cytokine production, increased susceptibility to apoptosis and tolerance induction, as well as increased susceptibility to the immunosuppressive effects of cyclosporin A and glucocorticoids (1)(2)(3)(4)(5)(6)(7). RTEs exiting the thymus are preferentially incorporated into the periphery, causing displacement of resident mature T cells, thereby maintaining the size of the peripheral naive T cell pool (8) and ensuring that the TCR repertoire is kept diverse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, IL7 is a promising candidate because: (1) it maintains the maturational state of T-cells [138] and (2) it promotes long-term T-cell survival in vitro [139]. Importantly, IL-7 does not switch T-cells to the memory phenotype [138,140] and triggers only a slight upregulation of activation markers in vitro [141].…”
Section: Targeting By Specific Vector-mediated Target Cell Activationmentioning
confidence: 99%
“…Or les lymphocytes T présents dans le sang de cordon, récents émigrants du thymus, présentent des caractéristiques d'activation distinctes de celles des cellules T périphériques de l'adulte. Une fois activées par l'IL-7, ces cellules, contrairement aux lymphocytes T de l'adulte [8,9], expriment le récepteur HTLV, les rendant ainsi théoriquement susceptibles à l'infection par HTLV [7]. Cette sensibilité à l'IL-7 des cellules T naïves pourrait ainsi expliquer la transmission préférentielle du virus HTLV de la mère infectée à l'enfant, même en l'absence de stimulation antigénique.…”
Section: > Htlv (Pour Human T-cell Leukemia Virus)unclassified